Small signal stability analysis of fixed speed wind generator including SDBR - Shawon, M.; Durra, A.; Muyeen, S.M. (2012)
This paper discusses small signal stability analysis of a grid connected fixed speed wind turbine driven induction generator (IG) including series dynamic braking resistor (SDBR). The stator windings of IG are directly connected to a power grid thorough a step-up transformer and transmission line, where SDBR is dynamically inserted in the generation circuit for short time during network disturbance. A detailed mathematical model of IG, transmission line, SDBR and grid is employed to derive the complete dynamic equation of the studied system. The purpose of SDBR is to mitigate the destabilizing depression of electrical torque and power during disturbance period. The power system small signal stability analysis is carried out by eigen value analysis. Modal and sensitivity analyses, participation factors are carried out to discover the relations between the modes and state variables. Finally, this paper presents an analysis of the dynamic behavior of fixed speed wind generator under voltage dip conditions with and without considering SDBR. The results of these studies are verified by a time domain simulation model developed in MATLAB/SIMULINK.